THE ADVANCE OF GLOBAL CAPITALISM AND THE CAPITULATION OF BRAZILIAN LABOR LAW (Revista Paradigma, 2018)
In this paper we analyze the current process of the surrender of social rights in Brazil in the view of historical classes, that lead to clarify the commitment of global capitalism in modern times and the protection as opposed to the instability of labor relations. We seek to gain a better understanding of the type of relationship that exists between the market society, the welfare state and democracy, that has shaped the National State's innovation plan. However, the experience of fascism has shown that its power, under certain circumstances, can be used to establish a totalitarian system. The thematic profile of this research is the critical theory of reality which is present in the bibliography and in the phenomenological approach involving outsourcing in its current form. The results point to the progress of globalization and a gradual process of deconstruction of the social project, especially the parts of which that are of labor nature and of the very idea of ​​citizenship.